Aspergillus flavus and cancer risks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Lethal aflatoxin secreted by the mould Aspergillus flavus, poses a significant risk of liver cancer throughout the world. Approximately a quarter of the food produced by tropical countries may contain this chemical. Until now, there has been no easy...